37.6k views
5 votes
Expand [a/3-b/6-1]^2

User Ddelange
by
5.0k points

2 Answers

3 votes

Answer:

(a/3


( (a)/(3) - (b)/(5) ) {}^(2)


\frac{ {a}^(2) }{9} - (2ab)/(15) + \frac{b {}^(2) }{25}

User Florian Gutmann
by
4.8k points
4 votes

Answer:

Explanation:

(x + y +z)^2 = x² + y² + z² + 2xy + 2yz + 2zx

x = a/3

y = -b/6

c = -1


[(a)/(3)-(b)/(6)-1]^(2)=((a)/(3))^(2)+((-b)/(6))^(2)+(-1)^(2)+2*(a)/(3)*(-b)/(6)+2*(-b)/(6)*(-1)+2*(a)/(3)*(-1)\\\\\\=(a^(2))/(9)+(b^(2))/(36)+1-(ab)/(9)+(b)/(3)-(2a)/(3)

User AllDayer
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.